Strategi Pengelolaan Usaha Sosial Non-Profit dalam Meningkatkan Kemandirian Masyarakat - Saraswati Saraswati; Santi Sukmaeni; Ilyas Aziz Firdaus (Jurnal Simki Economic, 2026)
Non-profit social enterprises play a strategic role in community empowerment and increasing economic independence. This study aims to analyze effective management strategies for non-profit social enterprises in increasing community independence. The research method used a descriptive qualitative approach, with data collection techniques through literature studies and observations of social enterprise management practices. The results indicate that effective management strategies include: (1) human resource capacity development; (2) financial sustainability through funding diversification; (3) network development and collaboration; (4) social business model innovation; and (5) social impact measurement. This study concludes that professional management of non-profit social enterprises with a social impact orientation can increase community economic independence in a sustainable manner.